Writers, Readers, and Erasers of Histone Ubiquitylation in DNA Double-Strand Break Repair - Smeenk, Godelieve; Mailand, Niels (Frontiers in Genetics, 2016)
DNA double-strand breaks (DSBs) are highly cytotoxic DNA lesions, whose faulty repair may alter the content and organization of cellular genomes. To counteract this threat, numerous signaling and repair proteins are recruited hierarchically to the chromatin areas surrounding DSBs to facilitate accurate lesion repair and restoration of genome integrity. In vertebrate cells, ubiquitin-dependent modifications of histones adjacent to DSBs by RNF8, RNF168 and other ubiquitin ligases have a key role in promoting the assembly of repair protein complexes, serving as direct recruitment platforms for a range of genome caretaker proteins and their associated factors. These DNA damage-induced chromatin ubiquitylation marks provide an essential component of a histone code for DSB repair that is controlled by multifaceted regulatory circuits, underscoring its importance for genome stability maintenance. In this review, we provide a comprehensive account of how DSB-induced histone ubiquitylation is sensed, decoded and modulated by an elaborate array of repair factors and regulators. We discuss how these mechanisms impact DSB repair pathway choice and functionality for optimal protection of genome integrity, as well as cell and organismal fitness.